Advances in Nanomaterials in Biomedicine - Ryabchikova, Elena I. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Advances in Nanomaterials in Biomedicine" provided a platform for more than 110 researchers from different countries to present their latest investigations in various fields of nanotechnology, new methods and nanomaterials intended for medical applications. Modern achievements in the field of nanoparticle-based diagnostics, drug delivery and the use of various nanomaterials in the treatment of diseases are presented in 11 original articles. The published reviews provide a comprehensive analysis of the current information on the use of nanomedicine in the treatment and diagnosis of cancer and liver fibrosis, in the field of solid tissue engineering and in drug delivery systems.